Satellite Tracking Can Inform Population-Level Dispersal to Foraging Grounds of Post-nesting Kemp’s Ridley Sea Turtles - Gredzens, Christian; Shaver, Donna J. (Frontiers in Marine Science, 2020)
Understanding how populations are distributed spatially can be an effective tool for conservation and management planning. This is especially true for threatened species of mobile marine megafauna, which can use vast expanses of the ocean as foraging and reproductive habitat. Additionally, the broad distributions of these species expose them to a wide variety of threats across their range. Marine turtles are one of these mobile marine megafauna taxa, with individuals making extensive migrations between nesting beaches and foraging grounds. However, it is not well understood how many marine turtle populations distribute themselves spatially at the population or species level. In this study, 178 post-nesting female Kemp’s ridley sea turtles were concurrently satellite tracked from their primary and major secondary nesting beaches between 2010 and 2017 to determine population- and species-level distribution of females to foraging grounds. Filtered tracks and switching state-space models were used to determine the proportion of the adult female population dispersing to, and foraging in, the northern and southern Gulf of Mexico. Fidelity to Gulf regions and foraging areas were also assessed. The majority of females dispersed to northern Gulf of Mexico foraging grounds indicating 82% of the adult female population may use the region to forage. Additionally, individuals displayed fidelity to regions, key foraging areas and migratory corridors over time. These results suggest that the northern Gulf of Mexico may provide the most important foraging areas for reproductively active females of the species and threats in the region may have a disproportionately higher impact on the adult female population, a population critical to the perpetuation and recovery of the species. Results highlight that continued bi-national recovery efforts are essential for recovery of Kemp’s ridleys, as most females nest on Mexican beaches and forage in USA waters. The methodologies used could be applied to conservation and management efforts of other imperiled mobile marine megafauna.